2013
DOI: 10.1017/jfm.2013.406
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between aquatic plants and turbulent flow: a field study using stereoscopic PIV

Abstract: A stereoscopic particle image velocimetry (PIV) system for use in shallow (∼0.5 m deep) rivers was developed and deployed in the Urie River, Scotland, to study the interactions between turbulent flow and a Ranunculus penicillatus plant patch in its native environment. Statistical moments of the velocity field were calculated utilizing a new method of reducing the contribution of measurement noise, based on the measurement redundancy inherent in the stereoscopic PIV method. Reynolds normal and shear stresses, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 51 publications
6
35
1
Order By: Relevance
“…4). In typical mixing layers and flows over aquatic canopies, it has been observed that sweeps (Q4 events) dominate at the top of a canopy, whilst ejections (Q2) dominate above the canopy [6,15], and we expect that this is also true here. The spatial patterns of , , , and imply that the flows around the algae at our field site are of intermediate relative submergence [16].…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…4). In typical mixing layers and flows over aquatic canopies, it has been observed that sweeps (Q4 events) dominate at the top of a canopy, whilst ejections (Q2) dominate above the canopy [6,15], and we expect that this is also true here. The spatial patterns of , , , and imply that the flows around the algae at our field site are of intermediate relative submergence [16].…”
Section: Resultssupporting
confidence: 57%
“…A horizontal shear layer with a width comparable to the patch width [13] develops between the water-surface and a specific depth within the canopy [3], while a near-vertical shear layer may also form at the patch edge [14]. Coherent vortices in these shear layers may dominate the turbulent flux of momentum across the patch edge [14], but the three-dimensionality of the wake and high background turbulence levels should disrupt periodic vortex formation [15]. At the downstream edge of a patch, velocity profiles slowly return to the undisturbed upstream condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-component vector fields are reconstructed from the two-component vector fields obtained for each camera using the local view angles obtained from a camera calibration procedure. The four-camera PIV system used here permits two independent estimates of each velocity component, which we use when calculating bulk statistics, correlation functions and spectra to reduce the contribution of measurement noise (for further details see Cameron et al 2013). …”
Section: Stereoscopic Particle Image Velocimetrymentioning
confidence: 99%
“…The Aberdeen PIV system has been developed in-house at the University of Aberdeen by Dr Stuart Cameron (Cameron 2011;Cameron et al 2013). The system comprises four cameras (DALSA 4M60, complementary metal oxide semiconductor sensor, 2352 pixel × 1728 pixel resolution at 62 frames per second (f.p.s.))…”
Section: The Particle Image Velocimetry Systemmentioning
confidence: 99%